Hail occurrence in Poland - Suwała, Katarzyna (Quaestiones Geographicae, 2011)
The main objective of this study was to present the spatial and temporal distribution of hail in Poland covering the period of 1973-2009. The analysis was based on the data for 23 meteorological stations published by The Institute of Meteorology and Water Management (1973-1980) and National Climatic Data Center (for the years 1981 to 2009). The results are presented with the maps of mean monthly and annual number of hail days, histograms of the seasonal variation of hail and trend lines in temporal variability of hail. It shows that in Poland the mean annual number of hail days varies from 1,3 near Suwałki to 10 near Hel. Most of the hail cases occurred in March, when the number of mean monthly hail days amounted almost 15. When it comes to temporal variability it is characterized by increasing tendency with the maximum at the beginning of 2000.